2021
DOI: 10.3390/ijms22073326
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Development of Antisense Oligonucleotides for Exon Skipping Restores Type XVII Collagen Expression in Junctional Epidermolysis Bullosa

Abstract: Intermediate junctional epidermolysis bullosa caused by mutations in the COL17A1 gene is characterized by the frequent development of blisters and erosions on the skin and mucous membranes. The rarity of the disease and the heterogeneity of the underlying mutations renders therapy developments challenging. However, the high number of short in-frame exons facilitates the use of antisense oligonucleotides (AON) to restore collagen 17 (C17) expression by inducing exon skipping. In a personalized approach, we desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Ablinger et al designed ASOs against COL17A1 exon 7 based on a patient with intermediate JEB carrying a variant in this exon. ASO treatment restored type XVII collagen expression in patient-derived primary cultured keratinocytes through exon 7 skipping [19]. The authors were also able to identify type XVII collagen expression at the cutaneous basal membrane in HSEs generated from JEB keratinocytes pretreated with COL17A1 exon 7 ASOs.…”
Section: Asos Targeting Mutated Exons In Epidermolysis Bullosamentioning
confidence: 93%
See 2 more Smart Citations
“…Ablinger et al designed ASOs against COL17A1 exon 7 based on a patient with intermediate JEB carrying a variant in this exon. ASO treatment restored type XVII collagen expression in patient-derived primary cultured keratinocytes through exon 7 skipping [19]. The authors were also able to identify type XVII collagen expression at the cutaneous basal membrane in HSEs generated from JEB keratinocytes pretreated with COL17A1 exon 7 ASOs.…”
Section: Asos Targeting Mutated Exons In Epidermolysis Bullosamentioning
confidence: 93%
“…Extensive research into splice-modulating antisense oligonucleotide therapies has led to the approval of several ASO drugs by the FDA [13] and/or EMA, such as Nusinersen for spinal muscular atrophy (OMIM 253300) and Eteplirsen [14] and Viltolarsen [15] for Duchenne muscular dystrophy (OMIM 310200). Preclinical research into exon skipping for COL7A1 and COL17A1 has demonstrated its potential as therapy for EB as well [16][17][18][19].…”
Section: Exon Skippingmentioning
confidence: 99%
See 1 more Smart Citation
“…A double-blind, randomized, intra-subject, placebo-controlled clinical trial of an AON targeting this exon in DEB wounds (NCT03605069) is currently being assessed [43]. Although direct delivery of AON to skin cells in wounds is feasible, improving delivery into intact skin is also being addressed using cationic liposomes [44].…”
Section: Rna-based Therapymentioning
confidence: 99%
“…In the last few years, the use of gene-editing technologies has demonstrated promising results. In particular, the use of antisense oligonucleotides was useful to correct some point mutations in Duchenne Muscular Dystrophy [ 17 , 18 ] and Epidermolysis Bullosa [ 19 ].…”
mentioning
confidence: 99%